Suitability of Local Mango Cultivars for Pulp Based Products - Irene Varghese (Department of Home Science, College of Agriculture, 1997)
The present study entitled “Suitability of local mango cultivars for pulp based products” was taken up for optimising the protocols of developing mango pulp based products viz., Mango RTS beverage, Mango squash and Mango jam using six different cultivars of mango. The physical and processing characteristics, the chemical composition of different mango cultivars, the chemical and organoleptic qualities of fresh products as well as in the products with storage and also the cost – benefit analysis were investigated in this study. On assessing the physical and processing characteristics of wide range of variation was seen to occur among all the six different varieties of mango. The chemical composition was also found to differ from cultivar to cultivar. On visualising the acceptability of the developed products, it was observed that the variety Neelum was best suited for the preparations of RTS beverage. While the varieties Kottukonam and Neelum were adjudged to be the best for squash preparation. In the case of jam preparation, the variety Panchasara varikka and Kappa was found to be the most suitable. When the chemical parameters like acidity, pH and Tss in fresh products were considered, it was seen that the acidity content remained almost similar in all the RTS beverages, squashes and james prepared from different cultivars of mango whereas the pH content of the products prepared was found to vary according to the variety. The Tss content was also found to differ according to the variety. Assessment of changes in organoleptic qualities of pulp based products with storage, indicated a declining trend in all the quality attributes such as appearance, colour, flavour, taste, consistency and overall acceptability. When the changes in chemical constituents that occurs in pulp based products with storage was considered, it was ascertained that in RTS beverages the acidity and Tss content remained unaltered during the storage period of three weeks whereas a slight decline in pH was noted after second week or storage. In the case of squashes and jams a gradual increase in acidity was noted during the storage period whereas the pH showed a decreasing trend with storage. The Tss content remained unaltered during storage in the case of squashes and jams also. Evaluation of microbial contamination in the stored products revealed the presence of pencillium colonies in RTS beverages after three weeks of storage and colonies of aspergillus were seen in squashes and jams after four months of storage. Cost – benefit analysis revealed that the cost of RTS beverages ranged from Rs. 12.00 to 14.00 per litre, cost of squashes ranged from Rs. 24.00 to 26.00 and the cost of jams ranged from Rs. 22.00 to 24.00. Thus physico-chemical, organoleptic and shelf life assessment of the pulp based products utilizing local mango cultivars encourages the utilization of above in product development.